Gravitational memory in higher dimensions - Monica Pate; Ana-Maria Raclariu; Andrew Strominger (Journal of High Energy Physics, 2018)
Abstract It is shown that there is a universal gravitational memory effect measurable by inertial detectors in even spacetime dimensions d ≥ 4. The effect falls off at large radius r as r 3−d . Moreover this memory effect sits at one corner of an infrared triangle with the other two corners occupied by Weinberg’s soft graviton theorem and infinite-dimensional asymptotic symmetries.